2013
DOI: 10.1016/j.gaitpost.2013.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Excessive fluctuations in knee joint moments during early stance in sprinting are caused by digital filtering procedures

Abstract: Abstract:Inverse dynamics analyses are commonly used to understand movement patterns in all forms of gait. The aim of this study was to determine the effect of digital filtering procedures on the knee joint moments calculated during sprinting as an example of the possible influence of data analysis processes on interpretation of movement patterns. Data were obtained from three highly trained sprinters who completed a series of 30 m sprints.Ten different combinations of cut-off frequency were applied to the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…Quantifying average horizontal external power during just the first stance phase therefore provides a performance measure that is directly relevant to the analysed technique. For the kinetic inputs to the inverse dynamics analysis, the force platform data were downsampled to the sampling rate of the kinematic data (200 Hz), and filtered with a cut-off frequency of 24 Hz to prevent the generation of artefacts soon after impact (Bezodis et al, 2013;Bisseling & Hof, 2006;Kristianslund, Krosshaug, & van den Bogert, 2012). Using these filtered kinematic and kinetic data in combination with the individual-specific segmental inertia data, a 2D inverse dynamics analysis was undertaken (Elftman, 1939;Winter, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Quantifying average horizontal external power during just the first stance phase therefore provides a performance measure that is directly relevant to the analysed technique. For the kinetic inputs to the inverse dynamics analysis, the force platform data were downsampled to the sampling rate of the kinematic data (200 Hz), and filtered with a cut-off frequency of 24 Hz to prevent the generation of artefacts soon after impact (Bezodis et al, 2013;Bisseling & Hof, 2006;Kristianslund, Krosshaug, & van den Bogert, 2012). Using these filtered kinematic and kinetic data in combination with the individual-specific segmental inertia data, a 2D inverse dynamics analysis was undertaken (Elftman, 1939;Winter, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…During the beginning of the stance phase, the hip exhibits extensor dominance, reaching peak extension torque at approximately 4.1 N·m·kg, before changing to a flexion moment toward the latter half of stance . The reported knee moments during stance vary much more between studies, which may be attributed to different filtering techniques utilized . Schache et al described an extension moment for the first half of stance, with a peak torque of 3.6 N·m·kg, before a flexion moment is produced toward late stance.…”
Section: Hip and Knee Kinetics During High‐speed Runningmentioning
confidence: 99%
“…17,31,32 The reported knee moments during stance vary much more between studies, which may be attributed to different filtering techniques utilized. 33,34 Schache et al 17,28 described an extension moment for the first half of stance, with a peak torque of 3.6 N·m·kg, before a flexion moment is produced toward late stance. However, other studies have reported a much more variable knee moment, sometimes switching several times from extension to flexion dominance throughout stance, although some researchers have argued that this may be an artifact of data processing.…”
Section: During High-speed Runningmentioning
confidence: 99%
“…Force signals were sampled at 1500 Hz, and were digitally filtered using a zero-lag fourth-order Butterworth filter (Winter, 2009). The chosen cut-off frequency was 10 Hz so as to match that applied to the kinematic data, a procedure that is consistent with published recommendations (Bisseling and Hof, 2006;Kristianslund et al, 2012;Bezodis et al, 2013).…”
Section: Experimental Data Collectionmentioning
confidence: 99%